Empire and religion: religious change in Greek cities under Roman rule - Muñiz Grijalvo, Elena; Cortés Copete, Juan Manuel; Lozano Gómez, Fernando (Impact of Empire, 2017)
"This volume explores the nature of religious change in the Greek-speaking cities of the Roman Empire. Emphasis is put on those developments that apparently were not the direct result of Roman actions: the intensification of idiosyncratically Greek features in the religious life of the cities (Heller, Muñiz, Camia); the active role of a new kind of Hellenism in the design of imperial religious policies (Gordillo, Galimberti, Rosillo-López); or the locally different responses to central religious initiatives, and the influence of those local responses in other imperial contexts (Cortés, Melfi, Lozano, Rizakis). All the chapters try to suggest that religion in the Greek cities of the empire was both conservative and innovative, and that the 'Roman factor' helps to explain this apparent paradox. Contributors are: Francesco Camia, Juan Manuel Cortés Copete, Alessandro Galimberti, Rocío Gordillo Hervás, Anne Heller, Fernando Lozano Gómez, Milena Melfi, Elena Muñiz Grijalvo, Athanasios Rizakis, Cristina Rosillo-López"--Provided by publisher